MENINGKATKAN KEMAMPUAN PEMAHAMAN DAN KONEKSI MATEMATIK SERTA MOTIVASI BELAJAR SISWA MADRASAH ALIYAH DALAM PEMBELAJARAN MELALUI PENDEKATAN SQ3R - Usuludin Usuludin (Tatar Pasundan: Jurnal Diklat Keagamaan, 2018)
This study aims to look at experimental results in a class by conducting initial and final tests and control classes by learning in Madrasah Aliyah through SQ3R approach (Survey, Question, Read, Recite and Review) as an effort to improve mathematical understanding and connection and learning motivation student. Respondents in this study were 74 students from class XI IPS MA in the city of Bandung. The instruments used include mathematical comprehension ability tests, mathematical connection ability tests and Miotiv questionnaire learning mathematics. From the research, it was found that classes that have mathematics learning use the SQ3R approach, understanding abilities and mathematical connections are better than ordinary classes, even though the two abilities are relatively low. While the motivation to learn mathematics in the experimental class is better than the control class with moderate differences. As for other things, it turns out that there is no association between understanding abilities and mathematical connections.  Key words: Mathematical comprehension ability, mathematical connection, learning motivation, SQ3R approach.